Illness Perceptions and Quality of Life in Childhood Cancer Survivors - Kohút, Adam; Koutná, Veronika; Blatný, Marek; Jelínek, Martin (Cancers, 2025)
BACKGROUND: Although illness perception (IP) is a widely recognised factor in the psychosocial adjustment to cancer, little is known about the impact of individual dimensions of IP. This study aims to analyse the relationship between individual dimensions of IP and quality of life (QOL) in childhood cancer survivors. METHODS: The sample consisted of 163 long-term survivors aged 11 to 25 who were administered the Brief Illness Perceptions Questionnaire and the Minneapolis-Manchester Quality of Life Scale. RESULTS: In the correlational analysis, all dimensions of IP were associated with individual dimensions of QOL, except for understanding and treatment control. The results of the hierarchical regression analysis controlling for demographic and medical factors showed that IP had predicted individual dimensions of QOL above and beyond these factors, with emotional response, concern, consequences and understanding being the most predictive dimensions. Several age-specific relationships between IP and QOL were also identified. CONCLUSIONS: Illness perceptions significantly contribute to explaining QOL of childhood cancer survivors above and beyond demographic and medical factors. These results may contribute to more effective targeting of psychosocial interventions promoting QOL of survivors.
Keywords: paediatric cancer; childhood cancer survivors; illness perception; quality of life